Life cycle assessment of novel heat exchanger for dry cooling of power plants based on encapsulated phase change materials. (1st August 2020) - Zhang, Lige; Spatari, Sabrina; Sun, Ying
Graphical abstract: Highlights: An air-cooled heat exchanger with high coefficient of performance (COP) is developed. The novel heat exchanger (HX) is based on encapsulated phase change material (EPCM). The EPCM HX is compared with wet cooling tower (WCT) and air-cooled condenser (ACC) Compared with the WCT, the EPCM HX reduces 13.3% GHG emission and 72% water usage. The EPCM HX achieves 2.5 × COP compared to ACCs at 11.5% reduced cost. Abstract: Cooling systems in power plants account for approximately 40% of total freshwater withdrawals in the U.S. Due to dwindling access to freshwater resources worldwide, continued operation of wet cooling systems poses a significant engineering challenge. To reduce water consumption, a novel air-cooled heat exchanger has been developed using encapsulated phase change material (EPCM) for dry cooling of power plants. Compared to traditional finned-tube air-cooled condensers, this novel EPCM heat exchanger improves the heat transfer coefficient and power plant efficiency while reducing the pressure drop and cooling system cost. Life cycle assessment (LCA) and techno-economic analysis (TEA) are used to evaluate the environmental and economic performance of EPCM heat exchangers from cradle-to-grave and to compare them to wet cooling and traditional air-cooled condensers. A thermodynamic model is developed to predict the EPCM heat exchanger performance for plant-scale operations. Equipment and construction costs for heat exchangers are estimated based on design parameters obtained from the thermodynamic model. Both process-LCA and economic-input–output LCA are used to simulate and test the sensitivity of EPCM alternatives with commercial wet and dry cooling technologies. We investigate options for EPCM end-of-life management upon retiring the heat exchanger and construct a process-based LCA model to estimate a greenhouse gas (GHG) emissions credit for recycling the EPCM. The life cycle GHG emission of the novel dry cooling technology is 1.16 kg CO2 eq. /MWh compared with the 1.1–4.3 kg CO2 eq. /MWh reported for commercial dry cooling technologies and consumes 9.5 L/MWhe of water for cradle-to-gate life cycle, which is significantly lower than that of wet cooling systems. The TEA shows many advantages of EPCM cooling technology over the state-of-art dry cooling solutions. Overall, the EPCM heat exchanger provides a better alternative compared to existing dry cooling and wet cooling technologies.